Cognitive Predictors of Child Second Language Comprehension and Syntactic Learning. Issue 3 (14th July 2021) - Pili‐Moss, Diana
Abstract: This study examined the role of child cognitive abilities for procedural and declarative learning in the earliest stages of second language (L2) exposure. In the context of a computer game, 53 first language Italian monolingual children were aurally trained in a novel miniature language over 3 consecutive days. A mixed effects model analysis of the relationship between cognitive predictors and outcomes in morphosyntax measured via a grammaticality judgment test (GJT) was performed. Relative to adults trained in the same paradigm, children with higher procedural learning ability (measured via an alternate serial reaction time task) showed significantly better learning of word order, although the effect size was small. Modeling accuracy in online sentence comprehension during the game also evidenced that higher procedural learning ability was positively associated with significantly better outcomes as practice progressed. By contrast, a composite measure of verbal and visual declarative learning ability did not predict L2 outcomes in either the GJT or the online measure. Abstract :